Research on Mass Center Identification for Gravitational Wave Detection Spacecraft with Guaranteed Laser Link Pointing Accuracy - Shen-Ao Wang; Huibo Zhang; Lin Cai; Ziming Wang; Yumin An (Remote Sensing)
The deviation of the center of mass of a gravitational wave detection satellite from its calibrated position can severely impact the accuracy of gravitational wave detection. Therefore, there is an urgent need to develop effective identification methods to achieve precise center of mass identification while ensuring the alignment of the laser link. To address this issue, this paper proposes a method for the center of mass identification of gravitational wave detection spacecraft that ensures the pointing accuracy of the laser link. A study on the relative attitude dynamics modeling of gravitational wave detection spacecraft is conducted, and the conditions for small, periodic spacecraft maneuvers that maintain laser link alignment are analyzed. A high-precision, high-stability center of mass identification method based on dual-model data fusion is proposed and simulated. The results show that this method can maintain the alignment precision of the laser interferometer arms within 10 nrad, while achieving a center of mass identification accuracy of 25 <semantics>μ</semantics>m. Compared to existing methods, this method improves the identification accuracy by an order of magnitude, demonstrating its feasibility for application in gravitational wave detection constellations. It provides theoretical support for the center of mass identification of gravitational wave detection spacecraft.